First implantable hemodynamic monitoring device placement in single ventricle fontan anatomy. Issue 2 (25th March 2016) - Bradley, Elisa A.; Berman, Darren; Daniels, Curt J.
Abstract : The Fontan anatomy leads to elevated central venous pressure along with chronic venous congestion and low cardiac output; this is felt to be responsible for deterioration of exercise tolerance and functional capacity over time. Real‐time hemodynamic evaluation of the Fontan anatomy has not been evaluated until now. Here, we report the technical aspects of the first two adult Fontan patients to undergo placement of an invasive hemodynamic monitor (IHM). We validate IHM readings with invasive pulmonary artery catheter derived hemodynamics in the Fontan and show successful home transmission of pulmonary artery hemodynamic tracings. This technology has the capacity to change current understanding of Fontan hemodynamics and treatment in patients with complex single‐ventricle anatomy. © 2016 Wiley Periodicals, Inc.